Marriage story [videorecording (DVD)] - Baumbach, Noah, 1969-; Johansson, Scarlett, 1984-; Driver, Adam; Dern, Laura; Alda, Alan, 1936-; Liotta, Ray; Hagerty, Julie (Criterion collection, 2020)
A love story about divorce. A marriage coming apart and a family coming together. A hilarious and harrowing, sharply observed, and deeply compassionate film from writer-director Noah Baumbach. Charlie is a charismatic New York theater director wedded to his work. Nicole is an actor who is ready to change her own life. Their hopes for an amicable divorce fade as they are drawn into a system that pits them against each other and forces them to redefine their relationship and their family.